IMPROVING THE STUDENTS’ ACADEMIC WRITING THROUGH RUBRICS AND PEER CORRECTION - I Made Wardhana (LITERA : Jurnal Bahasa Dan Sastra, 2017)
ABSTRACT This study attempted to find out the contributon of rubrics and peer correction as atechnique of teaching academic writing in the process of academic paragraph writing, in terms of,  what the students‟ perception on rubrics and peer correction is; what thestudents‟ writing achievement is through this technique; and what the correlation between the students‟ perception and their writing achievement is. Fifty one studentstaken from two classes, being exposed to the technique, were selected as the samples whose responses from the questionnaires showed that they had a very positive perceptiontowards the use of rubrics and peer correction in guiding them to write an academicparagraph; and there is a positive correlation between the students‟ positive perception and their academic paragraph writing achievement meaning that rubrics and peercorrection could help improve their writing achievement. Therefore, it could be suggested that rubrics could be applied as one of the favourable techniques to teachacademic paragraph writing as they were appropriate to be used as a guide to organize allcomponents of academic writing such as formats, punctuation and mechanics, content, organization and improve their ability in grammar and sentence structures (Oshima,2007) Keywords: rubrics, peer correction, academic writing.  ABSTRAK Studi ini mencoba untuk menemukan apa kontribusi rubrics dan peer correction dalamproses penulisan akademik, dalam hal bagaimana persepsi mahasiswa terhadap rubrics dan peer correction; bagaimana nilai penulisan paragraf akademik mahasiswa denganteknik ini, apakah ada korelasi antara rubrics dan peer correction dengan peningkatan nilai penulisan paragraf akademik mereka. Lima puluh satu mahasiswa yang diambil dari2 kelas yang diekspos dengan teknik ini dipilih sebagai sampel, yang responnya terhadapkuesioner menunjukkan bahwa mereka mempunyai persepsi yang sangat positif terhadap rubrics sebagai pedoman pengoranisasian penulisan paragraf akademik; dan peercorrection meningkatkan kemampuan grammar dan structure; serta terdapat korelasi positif antara persepsi mereka terhadap rubrics dan peer correction dengan prestasipenulisan paragraf akademik, yang berarti bahwa rubrics dan peer correction dapatmeningkatkan kemampuan penulisan akademik mereka; sehingga bisa direkomendasikan bahwa rubrics dapat dipakai sebagai salah satu teknik yang baik untuk meningkatkankemampuan penulisan paragraf akademik. Kata kunci: rubrics, peer correction, penulisan akademik paragraf.